UMP collaborates with industries to strengthen WBL, career placement - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 15 February 2022 - Universiti Malaysia Pahang (UMP) has established a strategic collaboration with industries to strengthen networks in various fields, especially academic, research, innovation, and human resource development that will benefit the university the industry.